2007
DOI: 10.1111/j.1532-950x.2007.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lidocaine on Postoperative Jejunal Motility in Normal Horses

Abstract: Use of lidocaine as a prokinetic agent cannot be supported by this study in normal horses; however, results may differ in clinically affected horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…Lidocaine administration following exploratory laparotomy has been associated with reduced small intestinal diameter and peritoneal fluid accumulation [8], decreased duration of gastric reflux and hospital stay [7], and reduced incidence of post-operative ileus and improved survival [21]. However, in normal horses lidocaine causes decreased jejunal motility [6] and delayed gastrointestinal transit time after prolonged administration [22]. In this study, we observed no effects of a prolonged lidocaine CRI on gastrointestinal transit, except when combined with butorphanol.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine administration following exploratory laparotomy has been associated with reduced small intestinal diameter and peritoneal fluid accumulation [8], decreased duration of gastric reflux and hospital stay [7], and reduced incidence of post-operative ileus and improved survival [21]. However, in normal horses lidocaine causes decreased jejunal motility [6] and delayed gastrointestinal transit time after prolonged administration [22]. In this study, we observed no effects of a prolonged lidocaine CRI on gastrointestinal transit, except when combined with butorphanol.…”
Section: Discussionmentioning
confidence: 99%
“…Traut et al (2008) reviewed the evidence for the clinical efficacy of various prokinetics in man and concluded that there was no evidence of efficacy of erythromycin, cholecystokinin, cisapride, dopamine-antagonists, propranolol or vasopressin and inconclusive evidence for lidocaine and neostigmine [148]. Evidence of the prokinetic properties of lidocaine is contradictory; some studies demonstrate an increase in contractile activity [149,150], others fail to report any change [151] and one study reported an increase in faecal transit time following a continuous lidocaine infusion [152]. Evidence of the prokinetic properties of lidocaine is contradictory; some studies demonstrate an increase in contractile activity [149,150], others fail to report any change [151] and one study reported an increase in faecal transit time following a continuous lidocaine infusion [152].…”
Section: Prokineticsmentioning
confidence: 99%
“…Phase II has intermittently occurring spike bursts, and finally Phase III has spike bursts associated with each slow wave. (Milligan et al 2007) Spike bursts are action potentials superimposed on the slow waves which result in contraction of the intestinal muscular layer. (Davies and Gerring 1983) The individual components of the MMC, i.e.…”
Section: Clinical Application Of Lidocaine Proposed Mechanism Of Actionmentioning
confidence: 99%